Relações entre indicadores de qualidade do solo e a produtividade das culturas em áreas com agricultura de precisão - Santi, Antônio Luis (2007)
The estimative of yield variability is an important tool to soil management decisions and to investigate yield limiting factors. Tools of precision farming as yield mapping and soil sampling using GPS makes possible identify the spatial variability of the field. This study was carried out with the objective of identify the main relationship among soil indicators and yield crops. The research was carried out in two commercial farms under no-tillage system located in Rio Grande do Sul State, Brazil. The soil is Oxisol and the weather cfa wet following Koppen classification. In this work six yield mapping of soybean, wheat and maize were merged to allow the definition of management zones. Three zones were classified as low, medium and high yield. In each zone 5 points were located and soil fertility (P, K, Ca, Mg, basis saturation, pH, SOM) and soil physic indicators (water infiltration, soil aggregation, bulk density, soil compaction) were investigated. The high yield zone, which had around 30% of total area, and the yield achieved was close to obtained in research plots. The soil fertility evolution was determined by temporal soil sampling in a 1 ha grid. In relation to native grass and natural forest (reference treatments) the cropland showed high levels of P and K in 0 to 0.05 m. Also, the downward movement of Ca+2 and Mg+2 were observed in cropland, even with surface broadcast lime. The amount of fertilizer input and nutrient harvest removed allow to estimate the soil fertility evolution. In 0 to 0.10 m there was necessary apply 14 kg of P2O5 ha-1 to increase 1 mg dm-3 of P available by Melich-1. For K there was necessary appling 5.2 kg de K2O ha-1 to increase 1 mg dm-3 of K available by Melich-1. There was a close relationship among nutrient use efficiency map, water infiltration map and yield map. The water infiltration was the soil indicator that explains the higher percentage of yield variability. Following by the macroaggregates (> 4.76 mm), GMD, bulk density, soil resistance and microporosity. In general the soil fertility was high and therefore the relationship with yield variability was low. The precison farm tools were efficient to establish the relationship between soil indicators and crop yields.